Adiposity and cardiovascular outcomes in three‐year‐old children of participants in UPBEAT, an RCT of a complex intervention in pregnant women with obesity. Issue 3 (11th September 2020) - Dalrymple, Kathryn V.; Tydeman, Florence A. S.; Taylor, Paul D.; Flynn, Angela C.; O'Keeffe, Majella; Briley, Annette L.; Santosh, Paramala; Hayes, Louise; Robson, Stephen C.; Nelson, Scott M.; Sattar, Naveed; Whitworth, Melissa K.; et al.
Summary: Background: Maternal obesity is associated with offspring cardiometabolic risk. UPBEAT was a randomised controlled trial of an antenatal diet and physical activity intervention in 1555 women with obesity. The intervention was associated with lower gestational weight gain, healthier diet and metabolic profile in pregnancy, and reduced infant adiposity at six months. Objective: We have investigated whether the UPBEAT intervention influenced childhood cardiometabolic outcomes or was associated with sustained improvements in maternal lifestyle 3‐years after delivery. Methods: In UPBEAT mother‐child dyads at the 3‐year follow‐up, we assessed childhood blood pressure, resting pulse rate, and adiposity (body mass index, skinfold thicknesses, body fat, waist and arm circumferences) and maternal diet, physical activity, and anthropometry. Results: 514 three‐year‐old children attended the appointment (49% intervention, 51% standard care). There was no difference in the main outcome of interest, subscapular skinfold thickness, between the trial arms (−0.30 mm, 95% confidence interval: −0.92, 0.31). However, the intervention was associated with a lower resting pulse rate (−5 bpm [−8.41, −1.07]). There was also a non‐significant lower odds of overweight/obesity (OR 0.73; 0.50, 1.08). Maternal dietary improvements observed in the UPBEAT trial, including glycaemic load and saturated fat were maintained 3‐years postpartum. Conclusion: This study has demonstrated that an antenatal dietary and physical activity intervention in women with obesity is associated with lower offspring pulse rate and sustained improvement in maternal diet. Whilst larger than previous cohorts, there remains potential for bias from attrition and these findings require validation in future cohorts.